Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.15252/embj.2022112275
|View full text |Cite
|
Sign up to set email alerts
|

An ERAD‐independent role for rhomboid pseudoprotease Dfm1 in mediating sphingolipid homeostasis

Abstract: Nearly one-third of nascent proteins are initially targeted to the endoplasmic reticulum (ER), where they are correctly folded and assembled before being delivered to their final cellular destinations. To prevent the accumulation of misfolded membrane proteins, ERassociated degradation (ERAD) removes these client proteins from the ER membrane to the cytosol in a process known as retrotranslocation. Our previous work demonstrated that rhomboid pseudoprotease Dfm1 is involved in the retrotranslocation of ubiquit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In a recent study we have solved the structure of the Orm1 containing SPOTS complex and have proposed that a monomeric form is the predominant form in yeast cells (Schäfer et al , 2023). This could also explain why the two Orm proteins are differentially regulated by the EGAD pathway (Schmidt et al , 2019; Bhaduri et al , 2023). It is also noteworthy that the timing of the increase in LCB biosynthesis after 5 minutes of heat shock and the regulatory mechanism by the EGAD pathway are difficult to align.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study we have solved the structure of the Orm1 containing SPOTS complex and have proposed that a monomeric form is the predominant form in yeast cells (Schäfer et al , 2023). This could also explain why the two Orm proteins are differentially regulated by the EGAD pathway (Schmidt et al , 2019; Bhaduri et al , 2023). It is also noteworthy that the timing of the increase in LCB biosynthesis after 5 minutes of heat shock and the regulatory mechanism by the EGAD pathway are difficult to align.…”
Section: Discussionmentioning
confidence: 99%
“…The two Orm proteins also underlie different regulatory mechanisms. Only the Orm2 protein is a substrate for the endosome/Golgi associated degradation (EGAD) pathway that depends on its phosphorylation by Ypk1/2, export from the ER, ubiquitination and finally degradation via the proteasome (Schmidt et al , 2019; Bhaduri et al , 2023). In addition, it was suggested that upregulation of SPT activity is directly linked to the uptake of exogenous serine via the Gnp1 amino acid permease (Esch et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast and mammalian homologs of Hrd1 and Doa10 promote feedback-regulated degradation of sterol-biosynthetic enzymes as well as turnover of proteins implicated in triacylglycerol and low-density-lipoprotein synthesis (HAMPTON et al 1996;GARZA et al 2009;JO et al 2011;FORESTI et al 2013;STEVENSON et al 2016;HUANG AND CHEN 2023). Moreover, the ER-resident rhomboid pseudoprotease Dfm1 was recently shown to regulate the ER export and Golgi-associated degradation of Orm2, an inhibitor of sphingolipid biosynthesis (BHADURI et al 2022). Lipid bilayer stress activates the yeast and mammalian ER unfolded protein response (UPR) via a distinct mechanism than activation by unfolded proteins (JONIKAS et al 2009;PROMLEK et al 2011;THIBAULT et al 2012;VOLMER et al 2013;HALBLEIB et al 2017;HO et al 2020; XU AND TAUBERT 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2016; H uang and C hen 2023). Moreover, the ER-resident rhomboid pseudoprotease Dfm1 was recently shown to regulate the ER export and Golgi-associated degradation of Orm2, an inhibitor of sphingolipid biosynthesis (B haduri et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We termed this membrane protein degradation pathway e ndosome and G olgi a ssociated d egradation (EGAD) 7,20,28 . To reach the Golgi, Orm2 must no longer bind to the serine palmitoyl transferase complex (SPT, Lcb1/2) at the ER, and exit the ER in COPII carriers with the help of the derlin Dfm1 29 . EGAD of Orm2 contributes to the de-repression of SPT activity and thus helps to maintain sphingolipid homeostasis 7 .…”
Section: Introductionmentioning
confidence: 99%